2016
DOI: 10.3171/2016.6.focus16189
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting secondary normal pressure hydrocephalus: does it exist? A review

Abstract: OBJECTIVE There are several etiologies that can lead to the development of secondary normal pressure hydrocephalus (sNPH). The aim of this study was to evaluate the etiology, diagnosis, treatment, and outcome in patients with sNPH and to highlight important differences between the separate etiologies. METHODS A comprehensive review of the literature was performed to identify studies conducted between 196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 82 publications
1
60
0
Order By: Relevance
“…The better response to shunt surgery in sNPH (in comparison to iNPH) has also been emphasized in other studies [3]. The diagnosis of sNPH is based on a combination of clinical history, physical examination, and imaging studies [2]. In our patient, the clinical presentation was characterized by the classic triad of dementia, gait disturbance, and urinary incontinence.…”
Section: A Dramatic Improvement By Ventriculoperitoneal Shunt Surgerysupporting
confidence: 57%
See 1 more Smart Citation
“…The better response to shunt surgery in sNPH (in comparison to iNPH) has also been emphasized in other studies [3]. The diagnosis of sNPH is based on a combination of clinical history, physical examination, and imaging studies [2]. In our patient, the clinical presentation was characterized by the classic triad of dementia, gait disturbance, and urinary incontinence.…”
Section: A Dramatic Improvement By Ventriculoperitoneal Shunt Surgerysupporting
confidence: 57%
“…Approximately, 50% of the normal pressure hydrocephalus (NPH) cases occur in association with prior events that cause the development of this syndrome [1]. In the recent crucial report by Daou et al, it was concluded that sNPH should be differentiated from idiopathic NPH (iNPH) based on outcome and on clinical, pathophysiological, and epidemiological characteristics, but should not be considered as a separate entity [2]. The better response to shunt surgery in sNPH (in comparison to iNPH) has also been emphasized in other studies [3].…”
Section: A Dramatic Improvement By Ventriculoperitoneal Shunt Surgerymentioning
confidence: 99%
“…As the main pathophysiology of patients' symptoms is derived from excessive accumulation of CSF in cerebral ventricular systems, clinical improvement of iNPH can be achieved mainly by shunt implantation surgery aimed at diverting the flow and absorption of CSF. This results in ameliorations of up to 50% and 80% in the symptoms of NPH [38]. To select candidates for shunt surgery, prognostic information is gathered from clinical examination, neuroimaging, and CSF testing [3].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2000 [ 5 ] the term secondary NPH in contrast to idiopathic NPH has been used in the literature, and while the definition of iNPH previously was “just” the lack of an explanation [ 6 ], later studies [ 7 , 8 ] have shown, that both the pathophysiology, the type of expansion of the ventricular system [ 7 ], the epidemiological characteristics [ 9 ] and the prognosis after treatment [ 9 ] differs between iNPH and sNPH.…”
Section: Discussionmentioning
confidence: 99%